Minister Abu Jaafar bin Atiya and his role in the Almohad state 517-553 AH /1123-1158 AD - ورده, زينب (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The research includes talk about one of the most famous ministers in the Almohad state, and he contributed to the administration of the Almohad state, and he is the minister Abu Jaafar bin Attia, who assumed the position of scribe and then minister, and also led the military armies in Andalusia, from the beginning of the rule of the era of Abd al-Mu’min bin Ali until the end of His era, and Minister Abu Jaafar is considered the most prominent and famous man of the era of Abd al-Mu’min, despite being a Minister of Execution who did not have wide influence due to the power of Caliph Abd al-Mu’min and his dominance over the government, as he excelled in politics and leading armies in battles. He also excelled in writing and literature, so it was known that he was A writer and poet. Many researchers have linked the snitching of some senior statesmen to the killing of Vizier Abu Jaafar, as Vizier Abu Jaafar bin Attia was the victim of the jealousy of the highest people over the rapprochement between the Caliph and the Vizier, which later led to the Vizier being accused of being loyal to the Almoravids, and thus the Caliph’s distance from him. And he was killed as a result.